1986
DOI: 10.1159/000206021
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus Vegetative Endocarditis Complicated with Schizocytic Hemolytic Anemia in a Patient with Acute Lymphocytic Leukemia

Abstract: Aspergillus vegetative endocarditis developing in a patient with acute lymphocytic leukemia during the phase of hematological remission has led to a fatal outcome, complicated with severe hemolytic anemia with red cell fragmentation. Systemic aspergillosis may involve heart valves with underlying disorders, but seldom affects intact valves even in severely compromised hosts. Among such rare cases so far reported, only 2 cases have been documented in acute leukemia, despite a huge prevalence of pulmonary and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…Hemolytic anemia has been reported in only a few previous. [2][3][4][5][6][7] Maeda et al reported a 65-year-old female with hemolysis associated with streptococcal endocarditis of the mitral valve. 2 That patient had an underlying obstructive hypertrophic cardiomyopathy with a 115-mmHg pressure gradient in the left ventricular outflow tract and a moderate mitral regurgitation due to mitral valve prolapse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hemolytic anemia has been reported in only a few previous. [2][3][4][5][6][7] Maeda et al reported a 65-year-old female with hemolysis associated with streptococcal endocarditis of the mitral valve. 2 That patient had an underlying obstructive hypertrophic cardiomyopathy with a 115-mmHg pressure gradient in the left ventricular outflow tract and a moderate mitral regurgitation due to mitral valve prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…Nishiura et al described hemolytic anemia with Aspergillus endocarditis involving the mitral valve in a patient with acute lymphocytic leukemia. 3 Postmortem examination of their patient showed huge vegetations on the mitral valve, and they postulated that the rapid progression of vegetations resulted in a powerful turbulent flow that caused intravascular hemolysis. Naidoo et al also reported intravascular hemolysis with fragmented erythrocytes in a patient with isolated enndocarditis of the pulmonary valve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both mechanical hemolysis and autoimmune hemolysis have been described 2, 3, 4. Hsuan‐Li et al reviewed six cases of hemolytic anemia secondary to endocarditis; in all the cases, there was the presence of fragmented erythrocytes suggestive of intravascular hemolysis 5.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%